Decoy Nanozymes Enable Multitarget Blockade of Proinflammatory Cascades for the Treatment of Multi-Drug-Resistant Bacterial Sepsis - Xuancheng Du; Mingzhen Zhang; Huiting Zhou; Weijie Wang; Chengmei Zhang; Lei Zhang; Yuanyuan Qu; Weifeng Li; Xiangdong Liu; Mingwen Zhao; Kangsheng Tu; Yong-Qiang Li (Research, 2022)
Sepsis is a life-threatening organ dysfunction characterized by severe systemic inflammatory response to infection. Effective treatment of bacterial sepsis remains a paramount clinical challenge, due to its astonishingly rapid progression and the prevalence of bacterial drug resistance. Here, we present a decoy nanozyme-enabled intervention strategy for multitarget blockade of proinflammatory cascades to treat multi-drug-resistant (MDR) bacterial sepsis. The decoy nanozymes (named MCeC@MΦ) consist mesoporous silica nanoparticle cores loaded with CeO2 nanocatalyst and Ce6 photosensitizer and biomimetic shells of macrophage membrane. By acting as macrophage decoys, MCeC@MΦ allow targeted photodynamic eradication of MDR bacteria and realize simultaneous endotoxin/proinflammatory cytokine neutralization. Meanwhile, MCeC@MΦ possess intriguing superoxide dismutase and catalase-like activities as well as hydroxyl radical antioxidant capacity and enable catalytic scavenging of multiple reactive oxygen species (ROS). These unique capabilities make MCeC@MΦ to collaboratively address the issues of bacterial infection, endotoxin/proinflammatory cytokine secretion, and ROS burst, fully cutting off the path of proinflammatory cascades to reverse the progression of bacterial sepsis. In vivo experiments demonstrate that MCeC@MΦ considerably attenuate systemic hyperinflammation and rapidly rescue organ damage within 1 day to confer higher survival rates (>75%) to mice with progressive MDR Escherichia coli bacteremia. The proposed decoy nanozyme-enabled multitarget collaborative intervention strategy offers a powerful modality for bacterial sepsis management and opens up possibilities for the treatment of cytokine storm in the COVID-19 pandemic and immune-mediated inflammation diseases.